PERANCANGAN ARENA AQUATIC DI TANGERANG, TEMA : ARSITEKTUR KONTEMPORER - Mauludin Abdul Chanafi Wijaya; Anggraeni Dyah Sulistiowati (MAESTRO, 2020)
Designing Arena Aquatic In Tangerang is a place of concentration for activities and self-development for athletes aquatic and non-athletes in improving sports performance and training in Tangerang city, especially for sports Aquatic namely swimming, diving, water polo, diving and gymnastics lovely, which is where this place has a clinic or facility to match the standards arena of FINA (Fédération Internationale de Natation Federation) or the international swimming federation that includes several sports Aquatic, so that the athlete can adjust to match or arena that standard international. The concept of contemporary architecture is a flow of architecture in his day that characterizes a freedom of expression, the desire to display something different, and a flow of integration of several architectural streams [1]. This concept is characterized by a practical and functional design with simple geometric shape processing and the selection of neutral colors that are clean and synchronous with each other, the concept of space that seems open and has an open plan facade (open plan).